2020
DOI: 10.7554/elife.61552
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SARS-CoV-2 viral entry upon blocking N- and O-glycan elaboration

Abstract: The Spike protein of SARS-CoV-2, its receptor binding domain (RBD), and its primary receptor ACE2 are extensively glycosylated. The impact of this post-translational modification on viral entry is yet unestablished. We expressed different glycoforms of the Spike-protein and ACE2 in CRISPR-Cas9 glycoengineered cells, and developed corresponding SARS-CoV-2 pseudovirus. We observed that N- and O-glycans had only minor contribution to Spike-ACE2 binding. However, these carbohydrates played a major role in regulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
224
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(234 citation statements)
references
References 54 publications
10
224
0
Order By: Relevance
“…This maturation process is key for proper viral protein functions. For instance, Spike N-linked glycosylation is required for virus entry into the host cells impacting directly on Spike stability during its synthesis instead of its binding ability to the ACE2 receptor (10). These modifications might be also key for antibody recognition.…”
Section: Introductionmentioning
confidence: 99%
“…This maturation process is key for proper viral protein functions. For instance, Spike N-linked glycosylation is required for virus entry into the host cells impacting directly on Spike stability during its synthesis instead of its binding ability to the ACE2 receptor (10). These modifications might be also key for antibody recognition.…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 S protein possesses several documented O -glycosylation sites located at the hinge between the RBD and NTD domains and surrounding the furin cleavage site ( Antonopoulos et al, 2020 ; Gao et al, 2020 ; Sanda et al, 2020 ; Shajahan et al, 2020 ; Zhao P. et al, 2020 ). Blocking of O -glycosylation resulted in partial inhibition of SARS-CoV-2 cell entry in vitro , indicating the functional importance of O -glycans in the infection process ( Yang et al, 2020 ). Epithelial cells of the upper respiratory tract, nasopharynx, trachea and large bronchi, appear to be the main producers of virions involved in inter-individual transmission ( Wolfel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have predicted that spike N- glycans may modulate protein folding and multimerization 8 , conformational changes, binding to the ACE-2 human receptor and immunological shielding 5 . Also, it has been shown using recombinant proteins and pseudotyped viruses that mutations in certain N- glycosylation sites of the spike lead to reduced infectivity 10 , and that treatment with kifunensine or MGAT1 knockout to prevent the formation of complex N- glycans reduces pseudovirus infection 11 . However, the effects of altering N- glycosylation in SARS-CoV-2 virions remain undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…By mutating N- glycosylation sites, it has been shown that the absence of glycans on Asn 331 and Asn 343 , both within the RBD, resulted in a drastic reduction of pseudovirus infection 10 . In addition, knocking out MGAT1 gene, which encodes for N -acetylglucosaminyl-transferase, an essential enzyme in the formation of hybrid and complex N -glycans, also reduced invasion of pseudotyped VSV suggesting that hybrid and complex spike N- glycans may be of importance for this process 11 . Although SARS-CoV-2 cDNA clones have been available for months 12,13 , no study has yet used real virions to provide direct evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation